Elastic and optoelectronic properties of novel Ag3AuSe2 and Ag3AuTe2 semiconductors. (September 2016) - Faizan, M.; Murtaza, G.; Azam, Sikander; Khan, Saleem Ayaz; Mahmood, Asif; Yar, Abdullah
Abstract: Ag3 AuSe2 and Ag3 AuTe2 are interesting class of semiconducting materials. Here, elastic and opto-electronic properties of Ag3 AuSe2 and Ag3 AuTe2 semiconductors are studied in detail using density functional theory. Different schemes are selected to treat the exchange-correlation effects. The unit cell of the compounds is fully optimized and calculated cell constants are found in agreement to the existing experimental data. The calculated elastic constants and elastic moduli reveal that the compounds possess ductile nature and are elastically stable. It is found that both compounds are direct bandgap semiconductor with bandgap value of 1.009 eV for Ag3 AuSe2 and 0.551 eV for Ag3 AuTe2 . As the compounds have narrow and direct bandgaps, therefore optically active. The optical properties like reflectivity, absorption coefficient, energy loss function, refractive index including and complex dielectric function are studied in detail. The direct band gap nature of these compounds make them useful candidate for different devices applications.